Manajemen Pendidikan Pondok Pesantren dalam Membentuk Karakter Santri di Pondok Pesantren Putri Al Azhar Sidowayah Beji - Tsaniatul Badi’ah; Barnoto Barnoto (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The results showed that the management of Islamic boarding schools in shaping the character of students at the Al-Azhar Islamic Boarding School had gone quite well with careful planning with quite ideal and realistic targets. Management functions that include planning, organizing, implementing and supervising have been applied regarding the formation of students with character. As for the management of extra activities and environmental management in shaping the character of students, they still need further improvement. Among the obstacles encountered in the field are the lack of supervision of teachers who live in boarding schools so that the effectiveness in supervision is low, the lack of local learning, the capacity of the students' rooms are overloaded, and the lack of concern for students' parents for the advancement of education. However, these obstacles can be overcome in many ways, including: solid cooperation, deliberation and consensus building and building awareness among educators to advance education. While the character of the students who stand out and want to be improved through education management include; discipline, independence and responsibility